2002
DOI: 10.1007/s005350200053
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal lymphangioma with a duodenal lesion in an adult

Abstract: A multilocular-cystic and cavernous, retroperitoneal tumor was found in a 40-year-old man whose past medical history was unremarkable. On admission, he complained of a large and still growing intra-abdominal mass associated with dull pain and a low-grade fever. Laboratory findings revealed leukocytosis and C-reactive protein elevation, compatible with inflammation of the tumor. Percutaneous aspiration of the tumor was performed under transabdominal ultrasonographic guidance, and continuous drainage of fluid fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…White-colored spots on the surface have been reported in previous case reports [4, 5, 6] as well as in our case. In the present case, white liquid material flowed from the tumor when the white spots were grasped by biopsy forceps.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…White-colored spots on the surface have been reported in previous case reports [4, 5, 6] as well as in our case. In the present case, white liquid material flowed from the tumor when the white spots were grasped by biopsy forceps.…”
Section: Discussionsupporting
confidence: 87%
“…Macroscopically, duodenal lymphangiomas appear as submucosal tumors [4, 5, 6, 7, 8]. White-colored spots on the surface have been reported in previous case reports [4, 5, 6] as well as in our case.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Retroperitoneal cystic lymphangiomas sometimes had a close relationship to visceral organs. Fujishiro et al [13] reported a patient with a retroperitoneal lymphangioma with dense duodenal adhesion which necessitated pancreaticoduodenectomy. However, the patients in our study showed no retroperitoneal visceral organ invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphangioma, a benign tumor of lymphatics, rarely occurs in the abdomin, and most of them arise in the mesentery, omentum, mesocolon and retroperitoneum [6][7][8][9] . The incidence of lymphangioma in the intestinal wall is very low, and few cases of multiple colonic lymphangioma have been reported [1][2][3][4] .…”
Section: Discussionmentioning
confidence: 99%